2022
DOI: 10.1039/d2ob01282k
|View full text |Cite
|
Sign up to set email alerts
|

Copper(ii)-catalyzed oxidative ipso-annulation of N-arylpropiolamides and biaryl ynones with 1,3-diketones: construction of diketoalkyl spiro-trienones

Abstract: An unprecedented copper-catalyzed ipso-annulation reaction of N-(p-methoxyaryl)propiolamides with 1,3-diketones has been developed, which enables the assembly of diketo-alkylated spiro[4.5]trienones involving oxidative dearomatization in the presence of ammonium persulfate [(NH4)2S2O8] as...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 53 publications
1
6
0
1
Order By: Relevance
“…Inspired by the primary results of this photocatalytic oxidation of biaryl ynones, we next took the challenge of implementation of this strategy to other ynone systems (4). 21 Biphenyl N-arylpropiolamides are susceptible to exhibit synthetic versatility in radical chemistry and theoretically capable to undergo [1,1], [1,2], [1,5], and [2,5] cyclizations; some of the possibilities are designed in Figure 4 and details in Supporting Information. This diverse nature of the substrate in radical reaction condition prompted us to study the viability of the present annulation reaction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Inspired by the primary results of this photocatalytic oxidation of biaryl ynones, we next took the challenge of implementation of this strategy to other ynone systems (4). 21 Biphenyl N-arylpropiolamides are susceptible to exhibit synthetic versatility in radical chemistry and theoretically capable to undergo [1,1], [1,2], [1,5], and [2,5] cyclizations; some of the possibilities are designed in Figure 4 and details in Supporting Information. This diverse nature of the substrate in radical reaction condition prompted us to study the viability of the present annulation reaction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To date, the cyclization of alkynes toward the synthesis of cyclic compounds has been effectively investigated [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Recently, the radical cascade cyclization of biaryl ynones has been demonstrated to be a useful approach to construct six-membered spiro[5,5]trienones [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ] with the development of different types of radical precursors ( Scheme 1 a–c). For example, Chen and Zhou reported an iron-catalyzed cascade silyl radical addition/6- exo -trig cyclization/dearomatization of biaryl ynones with silane, affording silylated spiro[5.5]trienones in good yields [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Chen and Zhou reported an iron-catalyzed cascade silyl radical addition/6- exo -trig cyclization/dearomatization of biaryl ynones with silane, affording silylated spiro[5.5]trienones in good yields [ 35 ]. In addition, several groups have demonstrated some elegant examples based on C-, N-, P-, S-, Si-, Se-centered radicals-induced cascade cyclization of biaryl ynones in the presence of transition-metal catalysts, oxidants or photocatalysts [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. For example, Duan and Yang reported the preparation of alkyl-functional spiro[5.5]trienone through alkylative dearomatization and the spirocyclization of biaryl ynones, respectively [ 29 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the importance of radical cascade reactions in establishing different reaction pathways, 6 the design of different substrates would enable novel methods for the synthesis of various chemical scaffolds. Based on our work involving the cascade thiofunctionalization/annulation of alkynes and alkenes, 7 we envisaged that biaryl enones are readily accessible and can act as radical acceptors followed by an intramolecular annulation with the aryl ring to provide phenanthrones. In a similar manner, recently, Li's research group reported an approach for the preparation of fluoro-alkylated phenanthrene-9(10 H )-ones from biaryl vinyl ketones (Scheme 1d).…”
Section: Introductionmentioning
confidence: 99%